von Willebrand disease type 1 in Doberman Pinscher dogs: genotyping and prevalence of the mutation in the Buenos Aires region, Argentina - Crespi, Julian Alejandro (2018)
von Willebrand disease (vWD) is the most common inherited coagulopathy in dogs, particularly in Doberman Pinschers. We developed a pyrosequencing-based assay to estimate the frequency of the c.7437G>A mutation associated with vWD type 1 in the Doberman Pinscher population of Buenos Aires, Argentina. We found a 0.41 frequency for the mutated allele, which varied significantly within families (family 1 = 0.43, family 2 = 0.58, unrelated animals = 0.35). The use of a popular founder male carrier of mutant allele A increased vWD incidence within a family and in the general population. The mode of inheritance was confirmed as autosomal dominant with incomplete penetrance. No differences were found between sexes and coat colors. Pyrosequencing was a good complement to clinical and coagulation tests for vWD type 1 diagnosis and a useful alternative for detecting the c.7437G>A mutation.